(untitled) (LEARNing Landscapes, 2021)
We examine a teacher’s read-aloud activity with her preschool students in India. Three vignettes show how this leading activity helps young children take part in socio-dramatic play, fostering their cultural-historical development. Collaborating as teacher and researcher, we consider students’ use of words, instances of object substitution, and exploration of social roles in the story being read aloud, to demonstrate the development of their higher psychological activity. Moreover, we contend that read-aloud activities in preschool are crucial for developing student learning during middle childhood.